Model for the promotion of the entrepreneurial culture as an instrument of Social Responsibility: Chilean case/Modelo para la promoción de la cultura emprendedora como instrumento de Responsabilidad Social: caso chileno (Encuentros, 2019)
In recent years, entrepreneurship has been a very discussed and highly developed topic, which has allowed to evolve in its conceptualization, firstly confronting two currents of thought; on the one hand, the Schumpeter School and, on the other, the Austrian School. We’ll understand entrepreneurship as: “an economic and social development engine and as such is capable of transforming the lives of people, and therefore our society”. Bearing this definition in mind, this paper deals with social entrepreneurship through the application of a model proposed as a process for the promotion of the entrepreneurial culture, which seeks to promote entrepreneurship in the first phase of the entrepreneurial process, as a valid and sustainable alternative to achieve economic autonomy in women victims of intrafamily violence of Women’s Centers from the region of Valparaiso, establishing the culture and entrepreneurial spirit in women, complying with social responsibility, both public and privateKeywords: Social Entrepreneurship; Gender Violence: Entrepreneurial Skills; Social Responsibility.